MILITARIZATION AND LOCAL RESISTANCE : HISTORY OF TNI INTERVENTIONS IN PAPUA CONFLICT SINCE INTERGRATION 1969 - Amatullah, Alif Adhar (JURNAL MAHATVAVIRYA, 2025)
Purpose of This study clearly underlines its originality by examining the history of Indonesian National Army (TNI) intervention in Papua and the dynamics of community resistance over the past five decades. The goal is to understand the pattern of state policy involving militarization, its impact on local communities, and how resistance is formed in response to such policies. Design/Methodology/Approach Study Approach used is historical qualitative, relying on archival studies, document analysis, and semi-structured interviews. This method ensures empirical data-based analysis and the relevance of historical context to the dynamics of Papua conflict. Findings of The study identified consistent government patterns in securitization policies, political repression, and social control, strengthened by military presence. This policy not only fails to resolve conflicts, but also strengthens community resistance and extends the cycle of distrust between government and local communities. The Originality/Value of the study of The study of civil-military relations and conflict resolution, emphasizing the need for alternative approaches such as demilitarization and recognition-based dialogue towards local agencies. Practically, these implications emphasize the importance of more inclusive and humanist policy reforms to ease tensions in Papua.